Adsorption-enhanced hydrolysis of glucan oligomers into glucose over sulfonated three-dimensionally ordered mesoporous carbon catalysts. Issue 24 (24th October 2016) - Dornath, Paul; Ruzycky, Stephen; Pang, Shintaro; He, Lili; Dauenhauer, Paul; Fan, Wei
Abstract : The hydrolysis of cellulose and β(1 → 4) oligosaccharides on carbon catalysts is a promising approach for the selective production of glucose from cellulose and its derivatives. Abstract : The hydrolysis of cellulose and β(1 → 4) oligosaccharides on carbon catalysts is a promising approach for the selective production of glucose from cellulose and its derivatives. In this study, a structure–property relationship was developed for the hydrolysis of water soluble glucan oligomers over three dimensionally ordered mesoporous (3DOm) carbon with sulfonic acid groups. It was found that the number of sulfonic acid groups on 3DOm carbon catalysts and their adsorption properties need to be optimized to maximize the hydrolysis of water soluble glucan oligomers. The adsorption capacity of glucan oligomers on 3DOm carbon increases with their chain length, which can be attributed to two molecular behaviors: (a) long glucan oligomers adsorbed on the carbon surface exhibit a dense packing structure compared with relatively small glucan oligomers; and (b) a part of a glucan oligomer "dangles" off the carbon surface due to its branched structure. It was found that the adsorption enthalpy and entropy increased with increasing the chain length of the glucan oligomers, which favors the hydrolysis reaction to produce glucose over the carbon catalysts.